2012
DOI: 10.1152/ajpendo.00249.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt signaling pathway effector TCF7L2 is upregulated by insulin and represses hepatic gluconeogenesis

Abstract: Certain single nucleotide polymorphisms (SNPs) in transcription factor 7-like 2 (TCF7L2) are strongly associated with the risk of type 2 diabetes. TCF7L2 and ␤-catenin (␤-cat) form the bipartite transcription factor cat/TCF in stimulating Wnt target gene expression. cat/ TCF may also mediate the effect of other signaling cascades, including that of cAMP and insulin in cell-type specific manners. As carriers of TCF7L2 type 2 diabetes risk SNPs demonstrated increased hepatic glucose production, we aimed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 42 publications
5
76
1
1
Order By: Relevance
“…We were unable to determine whether the regulation of TCF7L2 expression in livers of diabetic patients involved different mechanisms related to hyperglycaemia or insulin resistance, or whether the higher TCF7L2 expression levels were a consequence of other confounding factors such as differences in medication of type 2 diabetic individuals. Recent reports have shown that mouse TCF7L2 expression is insulin-responsive [20,22] and that in insulin-resistant mice expression of the short and medium C-terminal transcripts (e.g. including T3 and T5) was reduced [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We were unable to determine whether the regulation of TCF7L2 expression in livers of diabetic patients involved different mechanisms related to hyperglycaemia or insulin resistance, or whether the higher TCF7L2 expression levels were a consequence of other confounding factors such as differences in medication of type 2 diabetic individuals. Recent reports have shown that mouse TCF7L2 expression is insulin-responsive [20,22] and that in insulin-resistant mice expression of the short and medium C-terminal transcripts (e.g. including T3 and T5) was reduced [21].…”
Section: Discussionmentioning
confidence: 99%
“…An initial study of alternatively spliced Mature mRNA transcript Transcript number N-terminal C-terminal TCF4 nomination [13] Major pancreatic and liver TCF7L2 isoforms [12 [19]. TCF7L2 expression is highest in pericentral hepatocytes, where gluconeogenesis is low [20]. As evidence that TCF7L2 affects liver glucose metabolism [20][21][22] is accumulating, we sought to further characterise the expression of alternative human TCF7L2 transcripts in livers of normoglycaemic and type 2 diabetes individuals genotyped for rs7903146.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following pivotal studies indicating that the transcription factor 7-like 2 (TCF7L2) is an important risk gene for the development of type 2 diabetes (T2D) (1), great efforts have been made to explore its role as a Wnt signaling molecule in pancreatic b-cells and other tissues including liver (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Although several investigations suggested that TCF7L2 negatively regulates hepatic gluconeogenesis (8,10,11,17), one recent study (7) reported that liver-specific knockout of TCF7L2 reduced hepatic glucose production (HGP), while hepatic overexpression of TCF7L2 increased HGP.…”
mentioning
confidence: 99%